2021
DOI: 10.3389/fimmu.2021.644982
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between the Intestinal Microbiota and Acute Graft-Versus-Host Disease: Experimental Evidence and Clinical Significance

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative therapy for many hematological disorders and autoimmune diseases, but acute graft-versus-host disease (aGVHD) has remained a major obstacle that limits allo-HSCT and exhibits a daunting mortality rate. The gastrointestinal system is among the most common sites affected by aGVHD. Experimental advances in the field of intestinal microbiota research enhanced our understanding - not only of the quantity and diversity of intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 162 publications
0
10
0
Order By: Relevance
“…Moreover, these bacterial families have been identified as reservoirs of antibiotic resistance genes, further complicating their clinical outcome. The members of these bacterial families were often associated with higher mortality after HSCT and FN as well as GvHD development 51 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these bacterial families have been identified as reservoirs of antibiotic resistance genes, further complicating their clinical outcome. The members of these bacterial families were often associated with higher mortality after HSCT and FN as well as GvHD development 51 53 .…”
Section: Resultsmentioning
confidence: 99%
“…However, A prospective study reported a different result in which the microbiome on the ocular surface was characterized by a loss of diversity in ocular GVHD patients ( 79 ). Both investigations indicated that the ocular surface microbial dysbiosis is involved in the underlying microbial mechanism of ocular GVHD, but further investigations are warranted to explore the concrete mechanisms and therapeutic targets ( 80 ). Other less prevalent characteristics include cicatricial conjunctivitis (a kind of chronic conjunctivitis with conjunctival fibrosis and scarring formation), cicatricial entropion(inversion of the eyelids caused by fibrosis and scarring of the eyelid), symblepharon(any adhesion between the palpebral and bulbar conjunctiva), ankyloblepharon (partial or complete adhesion of upper and lower eyelids), and lagophthalmos(an inability to close the eyelids), which could progress to conjunctival keratinization and punctual occlusion ( 26 ).…”
Section: Pathogenic Mechanism and Novel Therapeutic Targetsmentioning
confidence: 99%
“…The outcome of transplantation is adversely affected by graft-versus-host disease (GVHD) after HCT, and organ rejection after SOT. In this context, studies suggest that intestinal microbiota is dysregulated after HCT and in patients who develop GVHD, 1 and monitoring and remodeling of microbiota after HCT can lead to the development of novel diagnostic tools, such as new disease markers or novel therapeutics in the form of elements of gut microbiota. 2 Similarly, dysbiosis occurs after SOT 3 , and it is believed to be caused by immunosuppressive therapy, which while preventing rejection, predisposes the host to various complications, such as life-threatening infections, cancer, or metabolic syndrome.…”
Section: Focused Topicsmentioning
confidence: 99%